The Sexual Motives and Purposes In Evie Blake’s Valentina - Imron Wakhid Harits; Silvi Bella Fransisca (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2019)
This study focuses on Valentina’s and Belle’s sexual motives, purposes, and activities in Evie Blake’s novel, entitled Valentina. Hence, the theory of Psychology and Literature and the concept of sexuality are used by the researcher to analyze this novel. Furthermore, this study uses qualitative design. The researcher involves herself in collecting and analyzing the data. The data of this study are taken from the author’s narration and also the characters’ utterances. The result of this study reveals that Valentina’s love to her lovers, curiosity of sadomasochism, and sexual desire becomes her motives to have sexual activities. As for Belle’s sexual motives are her love to Santos and her sexual desire. Meanwhile, Valentina’s and Belle’s purposes in doing sex are to feel a sexual pleasure and an emotional satisfaction. In addition, Valentina also wants to have a baby from her lover, Theo. Hence, it is known the kinds of sexual activities which Valentina and Belle do and experience with their partners.